Reviving the Nation: A Lacanian Perspective on Trump’s MAGA Fantasy - Imelda Sianipar; Aarce Tehupeiory (Jurnal Ilmiah Hubungan Internasional, 2025)
This article analyses Donald Trump's power fantasies centered on his "Make America Great Again (MAGA)" campaign. In his 2017 inauguration, Trump depicted the U.S. as a nation in decline, needing restoration. This study shows that Trump’s MAGA narrative is crafted to address perceived national decay. Using descriptive qualitative methods and Lacan’s psychoanalytic theory, the research examines Trump's speeches and statements to understand this narrative. By attributing the nation's problems to external and internal pressures, the MAGA message aligns with public anxieties and creates antagonisms. The findings reveal that this narrative reinforces Trump's political power and shapes national identity with promises of returning to past greatness. Trump positions himself as a symbolic "Big Other," a savior who resolves perceived threats and restores order. The MAGA narrative taps into collective desires for identity, belonging, and control, uniting supporters through shared grievances and externalized blame. This appeal resonates with deep psychological needs, creating cycles of temporary satisfaction and deferred fulfillment, which sustains loyalty and hope. Keywords: Political Fantasies, National Revival, Make America Great Again, Lacanian Psychoanalysis, Antagonism